“It was one of those complicated cases”: health practitioners’ perspectives and practices of providing end-of-life care for people with profound intellectual and multiple disability - Hille Voss (BMC, 2021)
Abstract Background Due to developments in health and social care, people with profound intellectual and multiple disability (PIMD) are living longer than ever before, meaning they are increasingly experiencing life-threatening health conditions requiring palliative care. Little is known about providing end-of-life care for people with PIMD. The aim of this study was to explore health practitioners’ perspectives and practices relating to end-of-life decision-making and planning for people with PIMD. Methods Seven in-depth semi-structured interviews were conducted with health practitioners employed in a range of hospital and community services throughout Melbourne, Australia. Questions were designed to gather information about their experience, perceptions, and attitudes relating to people with PIMD during and at the end of their life. Each interview, ranging from 40 to 60 min in length, was audio recorded and transcribed. Inductive thematic analysis was used to analyse the data. Results Four main themes emerged: limited participation, bias, dignity, and quality of death. Health practitioners indicated that people with PIMD are frequently excluded from participating in decision-making related to end-of-life care. Participants discussed reasons for this exclusion including challenges with communication and cognition. Participants reported a need for additional support and guidance in providing care for people with PIMD at the end of life. Professional and family bias played a role in end-of-life decision-making for people with PIMD. Participants reported a disproportional focus by palliative care practitioners on physical as opposed to emotional and spiritual well-being for patients with PIMD at the end of life. Finally, participants reported that people with PIMD generally did not die in specialised palliative care settings, but in segregated supported living environments. Conclusions Due to negative perceptions of a person with PIMD’s decision-making capacity, people with PIMD are likely to be assessed as unable to express choice and preference regarding end-of-life care and are offered limited opportunity to be involved in their own end-of-life care. This research provides guidance for the development of training and professional development relating to people with PIMD at the end of life. It is hoped that this will increase the accessibility of end-of-life services for people with PIMD, ensuring that a respectful and dignified death can be a reality for all humankind regardless of disability.